Pengaruh Faktor Personal dan Attitude Terhadap Green Consumer Behavior Produk LGGreen Health Pada Masyarakat Kota Padang - Dani Fajrul Arisyi; Yunita Engriani (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - This study aims to analyze the influence of personal factors on green consumer behavior, the effect of attitudes on green consumer behavior and the influence of personal factors on attitudes.Methodology - This type of research is a causative descriptive study. The sampling technique was purposive sampling with a sample of 100 people from Padang City using the LG brand air conditioner. The analytical method used is path analysis. The data processing used in this study is using SPSS version 24.0.Finding - The results of the study can be concluded that (1) personal factors have a significant positive effect on green consumer behavior, (2) personal factors have a significant positive effect on attitudes, (3) attitudes have a significant positive effect on green consumer behavior. Keywords: Personal Factors, Attitudes, Green Consumer Behavior